The First Case(s) of Botulism in Vienna in 21 Years: A Case Report. (21st June 2012) - Vossen, Matthias Gerhard; Gattringer, Klaus-Bernhard; Wenisch, Judith; Khalifeh, Neda; Koreny, Maria; Spertini, Verena; Allerberger, Franz; Graninger, Wolfgang; Kornschober, Christian; Lagler, Heimo; Reitner, Andreas; Sycha, Thomas; et al.
Abstract : We describe two linked cases of botulinum toxin intoxication to provide the clinician with a better idea about how botulism cases may present since early diagnosis and treatment are crucial in botulism. Botulinum toxin is the strongest neurotoxin known. Methods: We review the available literature, the compiled clinical data, and observations. Results: After a slow onset of clinical signs a married couple living in Vienna presented with dysphagia, difficulties in accommodation, inability to sweat, urinary and stool retention, dizziness, and nausea. They suffered intoxication with botulinum toxin type B. Botulism is a rarely occurring disease in Austria. In the last 21 years there were only twelve reported cases. Conclusion: Both patients went to a general practitioner as well as several specialists before they were sent to and correctly diagnosed at our outpatient department. To avoid long delays between intoxication and diagnosis we think it is crucial to advert to the complex symptoms a nonsevere intoxication with botulinum toxin can produce, especially since intoxications have become rare occurrences in the industrialized societies due to the high quality of industrial food production.